The Development of Learner Activity Sheets Based on Argument Driven Inquiry Model With Socioscientific Issues Context to Improve Students Argumentation Skills - Agustina Dua Kuki; Kristiana Nathalia Wea; Petronela Ivoni Susanty (Jurnal Pijar MIPA (Pengkajian Ilmu dan Pengajaran Matematika dan Ilmu Pengetahuan Alam), 2025)
Learning by integrating argumentation skills has not been fully implemented in learning.  The purpose of this study was to develop a student activity sheet based on the Argument-Driven inquiry model with a socioscientific issue context. This research integrates the context of socioscientific issues as a stimulus for students in building scientific argumentation. This research method is the 4D model, which includes the define, design, develop, and disseminate stages. However, the stages of this research are limited to the development stage. The results showed that the student activity sheet was developed based on the learning stages of the Argument-Driven inquiry model, which is limited to the scientific argumentation phase. The study of socioscientific issues is adjusted to the learning subtopic of factors that affect the reaction rate. The data from the validation study of the Learner Activity Sheet is classified as a very valid category with a content validity score of 89%; the validity of the layout presentation aspect is 92% and the language aspect is 96%. Meanwhile, the students' response result shows that the level of satisfaction with the activity sheets is 96%, including the category of very satisfied. The improvement of students' argumentation skills was at a moderate level with an N-gain score of 0.64. Statistical test results show there is a significant difference between pretest and posttest scores with a P-value <0.05. Based on these results, it can be concluded that the LAS based on the Argument Driven Inquiry model with a socioscientific Issue context is valid, practical and effective for improving students' argumentation skills.